Promoting positive development among youth from refugee and migrant backgrounds: The case of Kicking Goals Together. (November 2020) - Pink, Matthew A.; Mahoney, John W.; Saunders, John E.
Abstract: Objectives: The purpose of this study was to explore the case of Kicking Goals Together (KGT), a programme that combines a football competition with a life skills education intervention to elicit Positive Youth Development (PYD) outcomes for youth from refugee and migrant backgrounds. The Holt et al. (2017) model of PYD through sport provided the framework for the analysis of the case. Methods: Semi-structured interviews were conducted with ten participants comprising six of the programme's participants and four stakeholders. A deductive-inductive content analysis was used to explore the individuals' perceptions and experiences, the PYD outcomes, and the climate and implicit and explicit processes that related to these outcomes. Findings: The KGT climate supported the making of new friends and meeting new people; provided supportive relationships with adults; while participants described parents as being proud, supportive, but distanced. Personal outcomes related to PYD included increased confidence, improved networking skills, and enhanced employment opportunities. The social outcomes included improved communication, development of intercultural understanding and acceptance, improved teamwork and leadership, and a greater sense of belonging to a wider and more inclusive community. Conclusion: Analysis of the findings provided support for the analytical generalisation (Smith, 2018) and value of the Holt et al. (2017) model. Specifically, in highlighting how the structure and climate of the KGT initiative supported PYD outcomes. An environment that celebrated cultural diversity, and where youth had access to adults who were "functional advocates" (Whitley, Massey, & Wilkinson, 2018, p. 121) was identified as key to the achievement of these outcomes. Highlights: Examines the KGT program for refugee and migrant youth. Explores utility of Holt et al. (2017) model of PYD through Sport. Supports analytical generalisation of the Holt et al. (2017) model. Traces how the KGT PYD climate and pathways led to PYD outcomes. Adults serving as 'functional advocates' for youth was key to PYD outcomes.